Integration of palliative care in services for children with life-limiting neurodevelopmental disabilities and their families: a Delphi study - Suzanne Guerin; Gemma Kiernan; Eileen Courtney; Regina McQuillan; Karen Ryan (BMC, 2020)
Abstract Background The aim of this study was to explore expert professionals' opinions on service provision to children under six with life-limiting neurodevelopmental disabilities (LLNDD), including the goals of care and the integration and coordination of palliative care in general and specialist services. Methods A Delphi design was used with three questionnaire rounds, one open-ended and two closed response rounds. Primary data collected over a six-month period from expert professionals with five years' (or more) experience in pediatric, intellectual disability and/or palliative care settings. Ratings of agreement and prioritization were provided with agreement expressed as a median (threshold = 80%) and consensus reported as interquartile ranges. Stability was measured using non-parametric tests. Results Primary goals of care were achievement of best possible quality of life, effective communication and symptom management. Service integration and coordination were considered inadequate, and respondents agreed that areas of deficiency included palliative care. Improvement strategies included a single care plan, improved communication and key worker appointments. Conclusions The findings suggest that services do not serve this group well with deficiencies in care compounded by a lack of information on available services and sub-optimal communication between settings. Further research is needed to develop an expert-based consensus regarding the care of children with LLNDD.